Agency, resistance and (forced) mobilities. The case of Syrian refugees in transit through Italy. - Denaro, Chiara (REMHU, Revista Interdisciplinar da Mobilidade Humana, 2016)
During the biennium 2013–2014 Syrian refugees started to reach Italy through Mediterranean seaborne migration routes, from Libya and Egypt. Their presence contributed to partially modifying the configuration of the incoming migration flows to Italy, both in terms of socio-demographic composition and access to the European asylum system. Data shows that most of the Syrian refugees who landed in Italy between 2013 and 2014 decided to pursue their journeys to Northern Europe, by overcoming the restrictions imposed by the Dublin Regulation. The article focuses on the phenomenon of transit, as an interesting standpoint from which to observe certain acts of agency and resistance, put in place by refugees in order to “choose the country where to live” (Denaro, 2016): the refusal to provide fingerprints during identification, the organization of hunger strikes, the secondary mobility per se. Moreover, the article attempts to shed light on the relational and socio-political context in which these practices have taken shape, by focusing on the construction of relationships with activists and volunteers, and the (explicit and tacit) processes of negotiation which refugees conducted with police authorities and other stakeholders. Durante o biênio 2013-2014 refugiados sírios começaram a chegar à Itália, através de rotas migratórias marítimas no Mediterrâneo, desde a Líbia e o Egito. A presença deles contribuiu a modificar parcialmente a configuração dos fluxos imigratórios na Itália, em termos de composição sócio-demográfica e acesso ao sistema europeu de asilo. Os dados mostram que a maioria dos refugiados sírios que desembarcaram na Itália entre 2013 e 2014 decidiu prosseguir a viagem para o Norte da Europa, superando as restrições imposta pelo regulamento de Dublin. O artigo versa sobre o fenômeno do trânsito, como um ponto de vista interessante para observar certos atos de agência e resistência, postos em prática por refugiados a fim de “escolher o país onde viver”: a recusa de fornecer impressões digitais durante a identificação, a organização de greves de fome, a própria mobilidade secundária. Além disso, o artigo tenta lançar luz sobre o contexto relacional e socio-político em que estas práticas têm tomado forma, colocando em foco a construção de relacionamentos com ativistas e voluntários, e os processos (explícitos e implícitos) de negociação que os refugiados realizam com autoridades policiais e outras partes interessadas.